1995
DOI: 10.1055/s-2007-973028
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Proliferative Response to 2.5 Hours of Running

Abstract: The effect of 2.5 h of treadmill running at 75.6 +/- 0.9% VO2max on circulating leukocyte and lymphocyte subpopulations, epinephrine and cortisol concentrations, and the Con A-induced lymphocyte proliferative response was investigated in 22 experienced marathon runners (VO2max 57.9 +/- 1.1 ml.kg-1.min-1, age 38.7 +/- 1.5 yrs). Blood samples were taken 15 min before (07.15h) and immediately after exercise (10.00h), with three more samples taken during 6h of recovery (11.30, 13.00, 16.00h). Ten sedentary control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
62
1
10

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 4 publications
11
62
1
10
Order By: Relevance
“…The NLR is recognized as an index to assess exercise stress (Gleeson and Bishop 2000). Several previous studies have reported that the NLR increases after intense exercise (Nieman et al 1995(Nieman et al , 1999Makras et al 2005;Davison and Diment 2010;Lancaster et al 2003). In the present study, the NLR increased after exercise compared with that at Pre, and the increase continued until 4 h after exercise.…”
Section: Discussionsupporting
confidence: 62%
“…The NLR is recognized as an index to assess exercise stress (Gleeson and Bishop 2000). Several previous studies have reported that the NLR increases after intense exercise (Nieman et al 1995(Nieman et al , 1999Makras et al 2005;Davison and Diment 2010;Lancaster et al 2003). In the present study, the NLR increased after exercise compared with that at Pre, and the increase continued until 4 h after exercise.…”
Section: Discussionsupporting
confidence: 62%
“…27 Others have reported an even greater decrease after endurance race events. 39 The decrease in T-cell function is more prolonged than has been described after exercise of less than 1 h duration.…”
Section: Decrease In Mitogen-induced Lymphocyte Proliferationmentioning
confidence: 97%
“…3). [24][25][26][27][28][29][30][31] Several mechanisms appear to be involved, including exercise-induced changes in stress hormone and cytokine concentrations, body temperature changes, increases in blood flow, lymphocyte apoptosis and dehydration. Following prolonged running at high intensity, the concentration of serum cortisol is significantly elevated above control levels for several hours and this has been related to many of the cell trafficking changes experienced during recovery.…”
Section: High Neutrophil and Low Lymphocyte Blood Counts Induced By Hmentioning
confidence: 99%
“…It has been suggested that the relationship between exercise and URT infections follows a 'J' curve, with moderate and regular exercise improving the ability to resist infections (Nieman et al, 1993(Nieman et al, , 1998b and heavy acute or chronic exercise decreasing it (Nieman et al, 1990;Nieman, 1994;Castell et al, 1996). The evidence has shown that prolonged periods of intense training may lead to high numbers of neutrophil and low numbers of lymphocytes in blood counts (Nieman et al, 1995(Nieman et al, , 1998aPedersen et al, 1997), impaired phagocytosis (Nieman et al, 1997a) and neutrophilic function (Nieman et al, 2000a), decreased oxidative burst activity (Nieman et al, 1997a), natural killer cell cytolytic activity (NKCA) (Shinkai et al, 1993;Nieman, 1997) and mucosal immunoglobulin levels (Nieman et al, 2002a). Intense training or endurance exercise may also enhance release of pro-inflammatory cytokines such as tumour necrosis factor alfa (TNF-alfa), interleukin-1b (IL-1b) and interleukin-6 (IL-6), followed closely by anti-inflammatory cytokines, such as interleukin-10 (IL-10) and interleukin-1 receptor antagonist (IL-1ra) (Castell et al, 1997;Nieman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%